Implementasi Manajemen Keuangan di SMKN 1 Doloksanggul - Ningsih Pandiangan; Samuel Nababan; Christian Rosen Sitorus; Maris Simbolon; Radot Manalu (International Forum of Researchers and Lecturers, 2024)
This research aims to provide information and knowledge about the implementation of financial management carried out by SMKN 1 Doloksanggul, Humbahas District. The research methodused in this research is a qualitative method. Data collection techniques were carried out by researchers through interviews, note sheets. The research results obtained were that SMKN 1 Doloksanggul prepared a report card for 2024 before entering 2024 in November and December 2023 and the preparation of this report card was carried out by a team called the “BOS Team”. For school financial resources, the school principal forms various policies to obtain addiotional funds to be able to implement each program that has been prepared. Research conducted at SMKN 1 Doloksanggul shows that the implementation of school financial management is quite good.